Perkembangan Studi Bahasa Arab di Era Modern: Tantangan dan Peluang - Aufan Ni'am; Rido’i, Muhammad (Global Action and Education for Society, 2024)
This article examines developments in the study of Arabic in the modern era with a focus on the challenges and opportunities that arise as a result of technological advances and social change. The research uses descriptive analytical methods to evaluate a variety of literature and related data. The results show that despite the challenges, such as resource constraints, curriculum changes, and adaptation to new needs in language learning, there are huge opportunities that can be exploited. Using advanced technology and adapting to social dynamics can contribute to improving the quality of Arabic language learning. These findings highlight the importance of curriculum adaptation and the use of technology to meet challenges and exploit opportunities in developing Arabic study. With the right approach, Arabic education can become more effective, relevant, and responsive to changing times, paving the way for future progress in Arabic learning.